2015
DOI: 10.1002/ajoc.201402209
|View full text |Cite
|
Sign up to set email alerts
|

Photoaffinity Probes for Identification of Carbohydrate‐Binding Proteins

Abstract: Carbohydrate‐protein interactions mediate cellular signals, which are crucial in a diverse array of biological and pathological processes. Despite their importance, many carbohydrate‐protein interactions remain unknown due to inherent difficulties in studying them. With the aim to provide the first step in elucidating the biological roles of carbohydrates, photoaffinity labeling has been used as a promising chemical strategy for the detection and identification of carbohydrate‐binding proteins in their native … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 91 publications
0
10
0
Order By: Relevance
“…Carbohydrates constitute integral components of the cell machinery in the forms of polysaccharides, proteoglycans, glycoproteins, glycolipids, and glycosylated secondary metabolites and play crucial roles in a wide range of biological and pathological processes. 116 However, there are still many carbohydrate–protein interactions that remain unknown owing to transient and low-affinity interactions. 117 The use of carbene-mediated photocrosslinking of sugars represents a powerful strategy for investigating carbohydrate–protein interactions in their native context.…”
Section: Applications Of Cmpal For Biological Molecule–protein Intera...mentioning
confidence: 99%
“…Carbohydrates constitute integral components of the cell machinery in the forms of polysaccharides, proteoglycans, glycoproteins, glycolipids, and glycosylated secondary metabolites and play crucial roles in a wide range of biological and pathological processes. 116 However, there are still many carbohydrate–protein interactions that remain unknown owing to transient and low-affinity interactions. 117 The use of carbene-mediated photocrosslinking of sugars represents a powerful strategy for investigating carbohydrate–protein interactions in their native context.…”
Section: Applications Of Cmpal For Biological Molecule–protein Intera...mentioning
confidence: 99%
“…Labeled proteins of interest can be detected by fluorescence or chemical luminescence, or purified by avidin chromatography, and identified by mass spectrometric analysis. However, detection and identification of proteins of interest is often difficult because of the low efficiency of covalent bond formation with photoaffinity probes (<10%; Hashimoto & Hatanaka, 2008;Sakurai, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The structure of these probes must be close to that of the original ligand, but should also allow the introduction by bio-orthogonal reactions of chemical reporters, such as a fluorescent group or an isotope, and of an affinity tag for purification. To date, most glycoprobes reported in the literature are photoactivatable cross-linking compounds derived from mono- and disaccharides. , The synthesis of oligosaccharide probes is much less well studied. Among the few examples, gangliosides and Lewis X saccharidic portions have been successfully functionalized with AffiLight CHO, an aminoxy-biotinyl-phenyldiazirine reagent, but to the best of our knowledge, no biological study with these molecules has been reported to date.…”
Section: Introductionmentioning
confidence: 99%